Method of Parents in the Development of Child Prayers Attention Deficit Hyperactivity Disorder (ADHD) (Case Study of ADHD Children in Kulam Kemukiman Syamtarail Village, North Aceh) - Muhajir; Zahrul Mubarrak; Amiruddin; Khaidir; Fazil Saputra; Muhammad Ridha (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2019)
Concentration disorders accompanied by hyperactivity in children with ADHD are conditions that show symptoms of lack concentration, hyperactivity and impulsiveness that causes an imbalance of most of their life activities. This makes parents have difficulty in providing prayer guidance to children who have ADHD. Starting from this problem, the researcher tries to make a scientific about Parents' Method in the Development of Child Prayers Attention Deficit Hyperactivity Disorder (ADHD) (Case Study of ADHD Children in Kulam Kemukiman Syamtarail Village, North Aceh)." This study was conducted to describe the method parents in providing prayer services to children with ADHD in Kulam Kemukiman Syamtarail Village, North Aceh. This thesis research method uses the case study method which is a study that tries to examine individuals or a unit in depth with a qualitative approach. In collecting data researchers conducted observations and direct interviews within formants who have been used as samples, as well as documentation. While the analysis of data through observations in this thesis uses a theme analysis model technique where all data after being collected will be processed one by one. The results showed that ADHD children's prayer guidance involved all family members, namely the father, mother, siblings and cousins ​​of ADHD children. As for the methods carried out by the family in the guidance of prayers in children with ADHD can be concluded as follows:1. Intelegently; 2. Be haviour; 3. By monitoring.